Observed Mealtime Interactions, Meal Healthfulness, and Childhood Obesity Among Low‐Income Families. - Riley, Hurley O.; Peterson, Karen E.; Bauer, Katherine W.; Choe, Allison; Sturza, Julie; Rosenblum, Katherine; Kaciroti, Niko; Lumeng, Julie C.; Miller, Alison L. (Pediatric Obesity, 2026)
Introduction: Family mealtimes are promoted as a strategy to address childhood obesity; however, the joint associations of different mealtime elements with childhood obesity are not often considered. The current study investigated how mealtime family functioning and the nutritional quality of meals separately and jointly associate with childhood obesity. Methods: Typical mealtimes for 273 children (M age = 5.9 years, SD = 0.7 years) were video‐recorded. Observed mealtime family functioning, specifically mealtime structure and behaviour management, was coded from the video‐recorded mealtimes. The nutritional quality of meals was assessed using the Healthy Meal Index (HMI). Results: Logistic regression models indicated no independent associations between mealtime family functioning or nutritional quality of meals and child obesity status. However, the nutritional quality of meals moderated the association between mealtime structure and child obesity status (Interaction beta −0.06, SE 0.03; p = 0.04). Stratified analyses indicated that greater mealtime structure was associated with a higher likelihood of obesity among children served low‐nutritional‐quality meals (OR = 4.17, 95% CI 1.13–15.50, p = 0.03). Conclusions: Greater mealtime structure may be associated with an increased risk of childhood obesity when meals have low nutritional quality. Thus, various mealtime elements may interact in association with childhood obesity.